Entrepreneurial Activities as Antidotes to Retirement Penury in Nigeria: A Study of Southwestern States (Journal of Management and Social Sciences, 2019)
This paper examines entrepreneurial activities as alternative to retirement penury in Nigeria. The objectives of the study are to identify whether or not entrepreneurship, creativity and innovation are ways to retirement penury, seek ways of making entrepreneurship, creativity and innovation relevant at retirement and confirm or otherwise, the effects of entrepreneurial activities on retirement penury. The descriptive research design was employed. 106 respondents were randomly sampled with structured questionnaire. The result revealed that 82.08% of the respondents were in active service while 17.92% had retired with the implication that respondents in the study area should know what retirement plan entailed. The coefficient of determination (R2) obtained was 0.8145 indicating that 81.45% of antidotes for penury might be entrepreneurial activities. Moreover, the F-statistics computed for the test is 38.052 with the probability value of 0.0000 which is less than 5% critical value showing that entrepreneurial activities is statistically significant. The regression coefficients of EA and RLMR were -0.013 and -0.005 respectively. The null hypotheses were rejected because the p-values of EA and RLMR were 0.0003 and 0.018 respectively, all significant at 5% meaning that entrepreneurial activities are antidotes to retirement penury. The study concludes that retirees in any sector in Nigeria needed to engage in entrepreneurial activities at retirement.